Upaya Penetapan Hutan Adat Sebagai Hak Masyarakat Hukum Adat (MHA) di Kabupaten Lombok Utara - Jemarut, Wihelmus; Webliana B, Kornelia; Ichsan, Andi Chairil (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2024)
Legalization of customary forests is an effective way to resolve social conflicts within customary forest areas and grant access and management rights to Indigenous communities, thereby improving their welfare. This study analyzes the efforts to legalize Customary Forests in North Lombok Regency (KLU). The research method used is the legal empirical research method conducted from May to September 2024. Data were collected through observation, interviews and literature study. Interview informants were selected using purposive sampling technique. The results showed that efforts to legalize Customary Forest in KLU have only reached the process of legalization of the legal subject, namely the Customary Law Community (MHA). The process of legalization of MHA has started since the existence of KLU Regional Regulation No. 6 of 2020. Based on the identification results of the KLU MHA Identification Team, there are 43 (forty-three) Customary Forest areas in KLU. Four (4) of these areas are located within the Forest Estate. The forty-three Customary Forests are located in five (5) Customary Law Community units. The process of establishing these Customary Forests was supported by many parties including customary stakeholders, communities, and social institutions.